A View on Pathogenesis of ≪Vicious Cancer Progression Cycle≫ - Schwartsburd, Polina (Frontiers in Oncology, 2020)
Unrestricted tumor growth requires a permanent supply of glucose that can be obtained from cancer-stimulated hepatic glucose production and/or glucose redirecting from host insulin resistant tissues to cancer cells. This study proposes a mechanism based on metabolic and hormonal changes that may provoke glucose delivery to cancer cells through two interconnected “vicious cycles” whose continuous activity drives cancer progression. As follows from the proposed here feedback model, these “vicious cycles” result from cancer-mediated manipulation of host glucose sensors. The derived conclusions contribute to a better understanding of cancer pathogenesis and identifying potential therapeutic targets.